Implementation of Islamic Counseling Guidance in Forming Student Character in Madrasah - Hanifudin Hanifudin; Khoirotul Idawati (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the scope of counseling and guidance services available in Madrasahs, focusing on their relationship with character formation among students. Utilizing a descriptive qualitative approach with a case study model, the research aims to understand the dynamics of counseling and guidance services in shaping the character of students at Madrasah Tsanawiyah Al Anwar. Data were gathered from school principals, guidance and counseling teachers, and students through interviews, observations, and documentation. Analysis of the data involved data reduction, presentation, verification, and drawing conclusions. The findings reveal several key points: (1) Madrasahs offer various forms of counseling services encompassing orientation, individual, group, classical, learning, consultation, placement, content mastery, and career guidance; (2) there exists a strong correlation between counseling guidance and character development, with each reinforcing the other; (3) steps involved in using counseling and guidance services for character formation include group counseling, planning, execution, evaluation, and parental involvement; and (4) the effectiveness of counseling and guidance services in addressing issues and fostering character development in Madrasahs is evident through successful problem resolution. These findings underscore the active role played by counseling and guidance services in shaping student character through service provision activities.